2005
DOI: 10.1007/s11104-005-5675-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased Quantity and Quality of Coarse Soil Organic Matter Fraction at Elevated CO2 in a Grazed Grassland are a Consequence of Enhanced Root Growth Rate and Turnover

Abstract: The aims of this study were to determine whether elevated atmospheric CO 2 concentration modifies plant organic matter (OM) fluxes to the soil and whether any change in the fluxes can modify soil OM accumulation. Measurements were made in a grazed temperate grassland after almost 4 years exposure to elevated atmospheric CO 2 (475 ll l -1 ) using a Free Air CO 2 Enrichment (FACE) facility located in the North Island of New Zealand. Aboveground herbage biomass and leaf litter production were not altered by eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…Previous studies have shown that, under elevated CO 2 , especially C 3 plants (as used in our study) increase their total root exudation mainly through the expansion of their root systems (Rogers et al, 1994;Allard et al, 2005), yielding qualitative and quantitative changes in root exudation and other forms of rhizodeposition (Paterson et al, 1996;Hodge and Millard, 1998). Differences in plant exudation patterns between plants species is thought to exert differential selection in the rhizosphere, thereby shaping the size and structure of soil-borne communities (Bardgett et al, 1999;Smalla et al, 2001;Kowalchuk et al, 2002).…”
Section: Antibiotic-production Genesmentioning
confidence: 56%
“…Previous studies have shown that, under elevated CO 2 , especially C 3 plants (as used in our study) increase their total root exudation mainly through the expansion of their root systems (Rogers et al, 1994;Allard et al, 2005), yielding qualitative and quantitative changes in root exudation and other forms of rhizodeposition (Paterson et al, 1996;Hodge and Millard, 1998). Differences in plant exudation patterns between plants species is thought to exert differential selection in the rhizosphere, thereby shaping the size and structure of soil-borne communities (Bardgett et al, 1999;Smalla et al, 2001;Kowalchuk et al, 2002).…”
Section: Antibiotic-production Genesmentioning
confidence: 56%
“…Further, in some systems, forbs have been found to be one of the more CO 2 -sensitive plant functional types ). If root growth and turnover are considered, then there was a stimulation in plant biomass at elevated CO 2 that appeared to be strongest under conditions of low soil moisture in New Zealand (Newton et al 1996;Allard et al 2004). …”
Section: Mesic Grasslandsmentioning
confidence: 99%
“…In grass, the combination of higher belowground production and lower decay rates suggests that root biomass may be a significant contributor of soil C stocks compared with shrubs. However, higher turnover may also imply an increase in particulate organic matter (Allard et al 2005), which may be less lignified and easily decomposed in the long term.…”
Section: Production and Decomposition Of Rootsmentioning
confidence: 99%